Socio‐demographic differences in opinions about 2009 pandemic influenza A (H1N1) and seasonal influenza vaccination and disease among adults during the 2009–2010 influenza season. Issue 3 (9th May 2012) - Santibanez, Tammy A.; Singleton, James A.; Santibanez, Scott S.; Wortley, Pascale; Bell, Beth P.
Abstract : Background  In April 2009, a novel influenza A virus emerged in the United States. By the end of July, influenza A (H1N1) 2009 monovalent (2009 H1N1) vaccine had been developed, licensed, and recommended by the Advisory Committee on Immunization Practices. Initial target groups for vaccination were identified and the first vaccine was publicly available in early October 2009. Objective  This study examines socio‐demographic differences in opinions about 2009 pandemic influenza A (H1N1) (pH1N1) and seasonal influenza disease and vaccines and the association with receipt of influenza vaccinations during the 2009–2010 influenza season. Changes in opinions over the course of the pH1N1 pandemic were also examined. Methods  Data from the 2009 National H1N1 Flu Survey (NHFS) were analyzed. The NHFS was a CDC‐sponsored telephone survey initiated in response to the 2009 pH1N1 pandemic to obtain weekly within‐season estimates of vaccination coverage, opinions, and other information. Results  Opinions about influenza vaccine and disease varied significantly by race/ethnicity, income, and education level. In multivariable logistic regression analysis, adjusted 2009 H1N1 vaccination coverage was most strongly associated with opinions about the effectiveness of the vaccine and personal risk of disease, varying from 7 to 11% among adults who believed the vaccine to have low effectiveness and themselves at low risk of influenza, to 50–53% among those who thought vaccine effectiveness to be high and themselves at high risk of influenza. Conclusion  Improving communication about personal risk and the effectiveness of influenza vaccines may improve vaccination coverage. The findings of difference in opinions could be used to target communication.